2018
DOI: 10.1039/c8ra00501j
|View full text |Cite
|
Sign up to set email alerts
|

Highly porous and chemical resistive P(TFEMA–DVB) monolith with tunable morphology for rapid oil/water separation

Abstract: A facile preparation for a series of porous poly(2,2,2-trifluoroethylmethacrylate–divinylbenzene) P(TFEMA–DVB) foams is discussed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…The selection of a suitable surfactant to enhance the thermodynamic stability of HIPEs is of vital importance. It is worth noticeable that only a limited number of commercially available surfactants are able to give obtrusive stability to HIPEs . The stabilization of a particular emulsion system demands a thoughtful selection of surfactant to obtain the required hydrophilic‐lipophilic balance (HLB).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The selection of a suitable surfactant to enhance the thermodynamic stability of HIPEs is of vital importance. It is worth noticeable that only a limited number of commercially available surfactants are able to give obtrusive stability to HIPEs . The stabilization of a particular emulsion system demands a thoughtful selection of surfactant to obtain the required hydrophilic‐lipophilic balance (HLB).…”
Section: Resultssupporting
confidence: 92%
“…It is worth noticeable that only a limitedn umber of commercially available surfactants are able to give obtrusive stability to HIPEs. [46] Thestabilization of ap articulare mulsion system demands at houghtful selection of surfactantt oo btain the required hydrophilic-lipophilic balance (HLB).F irst of all, it was tried to prepare MMA HIPEs by carefully selecting various commercial surfactants.S PAN60, CTAB, SPAN80, SPAN85, HypermerB 246a nd Tween 80 were employedt oc heck their potentiali ns tabilization of MMA HIPEs through free radicalp olymerization. ExceptH ypermer B246, none of the other surfactants was able to stabilizee mulsion ( Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of stable uorinated emulsions is particularly difficult due to the limitations associated with available surfactants. 1,18,19 A series of surfactants were carefully selected to stabilize water/oil (w/o) emulsions using uorinated acrylate as a continuous phase monomer. HIPEs were then prepared using these conventional surfactants, i.e.…”
Section: Stability Of Hipe and Droplet Size Distributions With And Wimentioning
confidence: 99%
“…Inspection of the morphology of the porous materials post emulsion polymerization, showed that the average pore sizes of polyHIPE prepared with PLA were smaller than those produced without PLA, consistent with the observed (small) emulsion droplets sizes. The porous material prepared without PLA had the large pore structure of a conventional polyHIPE, 1,10,39 and the average pore diameter was 45.24 mm (Fig. 3A).…”
Section: Stability Of Hipe and Droplet Size Distributions With And Wimentioning
confidence: 99%
See 1 more Smart Citation